Analisa Daerah Lindung dan Grounding Pada Tower Transmisi Akibat Terjadinya Back Flashover - Renaldi P. Luntungan; Lily S. Patras; Glanny M.Ch. Mangindaan (Universitas Sam Ratulangi, 2018)
Abstract − Lightning is a natural phenomenon caused by the presence of electric charges in the atmosphere that has a very large current and a very short time, thus causing fatal damage especially on electrical equipment in the open air. Any lightning discharge occurring within the cloud, between clouds and clouds to the ground, will generate electrical radiation with a very wide frequency spectrum (in the order of kHz to MHz order). Therefore, lightning often causes interference in the transmission line. The disturbance caused by direct stroke on SUTT ground wire is a back flashover phenomenon. Back flashover phenomenon occurs when the voltage on the channel isolator is greater than or equal to the critical voltage of flashover (critical flashover) so that a flashover occurs in the isolator.From the analysis of grounding conditions on the tower No. 62 SUTT 70KV transmission Tomohon - Teling direction impacted Back Flashover, because the value of grounding measurement resistance is 7.1 Ω has a difference exceeding the standard value of grounding resistance of ≤ 5 Ω of the default value set.Keywords − Back Flashover, Ground wire, Grounding resistance Abstrak − Petir adalah suatu fenomena alam yang disebabkan karena adanya muatan elektrik di atmosfir yang memiliki arus sangat besar dan waktu yang sangat singkat, sehingga menimbulkan kerusakan yang fatal terutama pada peralatan listrik di udara terbuka. Setiap peluahan petir yang terjadi di dalam awan, antar awan maupun dari awan ke tanah, akan memunculkan radiasi elektrik dengan spektrum frekuensi sangat lebar (dalam orde kHz hingga orde MHz). Oleh sebab itu, petir seringkali menyebabkan gangguan pada saluran transmisi. Gangguan yang disebabkan oleh sambaran langsung (direct stroke) pada kawat tanah SUTT adalah fenomena back flashover. Fenomena back-flashover terjadi bila tegangan pada isolator saluran lebih besar atau sama dengan tegangan kritis lompatan api (critical flashover) sehingga lompatan api terjadi pada isolator tersebut.Dari hasil analisa kondisi grounding pada tower No.62 SUTT 70KV transmisi jurusan Tomohon – Teling berdampak terjadi Back Flashover, karena Nilai resistansi pengukuran pentanahan adalah sebesar 7,1 Ω memiliki perbedaan melebihi nilai standar resistansi pentanahan sebesar ≤ 5 Ω dari nilai standar yang di tetapkan.Kata kunci − Back Flashover, Kawat tanah, Tahanan pentanahan.